The study on factors that affects the customer satisfaction toward Kira Haq Global Marketing Sdn Bhd / Nor Afiqah Md Azman - Md Azman, Nor Afiqah (2017)
The purpose of this research is to investigate factors that influence customer satisfaction toward Kira Haq Global Marketing Sdn Bhd. and to recommend ways to improve customer satisfaction at Kira Haq Global Marketing Sdn Bhd. Problem statements derived from the problem that faced in Kira Haq Global Marketing Sdn Bhd. 100 set of questionnaire were distributed to Kira Haq customer to collect and analyze the data toward customer satisfaction. Data analysis was conducted using SPSS. Through the result, price is the most important factor that affects customer satisfaction. Kira Haq need improve their organization in order to maintain and increase number of customer toward their product and service. This study will give guideline to assist the company in enhance their business.